2019
DOI: 10.1002/term.2805
|View full text |Cite
|
Sign up to set email alerts
|

A simple and static preservation system for shipping retinal pigment epithelium cell sheets

Abstract: 433 Effect of the small compound TD -198946 on glycosaminoglycan synthesis and transforming growth factor β 3-associated chondrogenesis of human synovium-derived stem cells in vitro A simple and static preservation system for shipping retinal pigment epithelium cell sheets K. Hori, J. Kuwabara, Y. Tanaka, M. Nishida, N. Koide and M. Takahashi 459 DNA methyltransferases inhibitors effectively induce gene expression changes suggestive of cardiomyogenic differentiation of human amniotic fluid-derived mesenchymal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Because calcium ions are not present in saline, calcium dependent cell–cell adhesion was not retained in cell sheets preserved in saline ( Figure 2D ). In other studies, a retinal pigment cell sheet was preserved for 5 h ( Hori et al, 2019 ) and an oral mucosal cell sheet was preserved for 12 h ( Oie et al, 2014 ). Therefore, cell sheet quality can be maintained in HBSS for 2 days, which is long enough for stability studies and for transport throughout Japan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because calcium ions are not present in saline, calcium dependent cell–cell adhesion was not retained in cell sheets preserved in saline ( Figure 2D ). In other studies, a retinal pigment cell sheet was preserved for 5 h ( Hori et al, 2019 ) and an oral mucosal cell sheet was preserved for 12 h ( Oie et al, 2014 ). Therefore, cell sheet quality can be maintained in HBSS for 2 days, which is long enough for stability studies and for transport throughout Japan.…”
Section: Discussionmentioning
confidence: 99%
“…First, we preserved the cell sheets only at room temperature. Hori et al preserved retinal pigment epithelium cell sheets at 37°C ( Hori et al, 2019 ), and Kawazoe et al preserved skin grafts at 4°C ( Kawazoe et al, 2008 ). Therefore, optimization of temperature may be one of the key factors for long-term preservation of cell sheets.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated the successful shipment of femoral head tissue and Achilles tendon at -40˚C for at least 48 hours indicating that the safety and quality of human tissue could be maintained during transportation at during shipment [8]. Hori and colleagues have demonstrated a new technology for shipping RPE tissues at room temperature by using a heat insulating container to minimise the physical and chemical stress on the cells [10]. Additionally, a recent study has developed a new protocol for shipping retinal organoids at 37˚C to facilitate the preclinical studies in animal models and potentially transplantation by maintaining the viability of the tissue and preventing tissue damage [11].…”
Section: Introductionmentioning
confidence: 99%